Review and Analysis of The Operational Expenditure Budget of State Ministry/Institutions for The Economy and Maritime Affairs - shiddiq ardhi irawan (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2023)
The State Revenue and Expenditure Budget is an important instrument in controlling the economy from shocks both internal and external to the Indonesian Government. In managing the APBN, it is hoped that it will be able to expand more productive economic activities so that it can improve community welfare. One of the components of the APBN is state spending, which has increased from year to year. However, this increase was not accompanied by an increase in the quality of planning and budgeting in allocating State Ministries/Institutions expenditure budgets. The State Ministries/Institutions of operational expenditure allocations have also increased in line with increasing state spending. Based on the results of the review, in 2023 there will be a spending allocation that should not be included in State Ministries/Institutions operational goods spending amounting to IDR 576.4 trillion. This allocation can be reallocated to activities that benefit the community. Apart from that, this research also uses regression analysis, cluster analysis and confidence interval methods to calculate State Ministries/Institutions operational expenditure. From these results, there are four State Ministries/Institutions whose operational expenditure allocations are outside the limits determined based on the confidence interval value.